It’s Been the Best of Times: My Twenty-Year Retrospective on Adult Education - Juanita Johnson-Bailey (Adult Education Research Conference, 2015)
This essay presents a personal assessment of the ways in which the field of Adult and Continuing Education has succeeded and faltered during the last two decades and discusses how the field can address future challenges.